PREFERENSI AGROINDUSTRI TAHU DAN TEMPE DALAM PEMILIHAN BAHAN BAKU KEDELAI DI KOTA BANDAR LAMPUNG - Permata, Adistia Cahya; Rosanti, Novi; Haryono, Dwi (Lampung University, 2025)
The purpose of this study is to identify the attributes of soybeans, and to analyze the preferences of tofu and tempeh agro-industries in the selection of soybean raw materials in Bandar Lampung City. The research method used in this study was survey method. This research was conducted at the tofu and tempeh agro-industry in Bandar Lampung City. The location of the agro-industry was chosen purposively. The sampling technique used was probability sampling (stratified random sampling). The number of samples in this study ware 60 people. The analytical tools utilized to answer the first objective was qualitative descriptive analysis, and for the second objective was conjoin analysis. The results of the study indicate that soybean’s attributes considered by the owners of tofu and tempeh agro-industries in Bandar Lampung City are including size, shape, color, origin, and price. Tofu agro-industry preferences in Bandar Lampung City in the selection of soybean raw materials prefer to have soybeans that are imported with round shape, yellow color, medium size, high price, with the most important attribute of being the origin attribute. The preferences of tempeh agro-industry in Bandar Lampung City in the selection of soybean raw materials prefer to have imported soybeans with oval shape, white color, large size, low or medium price, with the most important attribute being the price attribute. Keywords: conjoin, tempe, and tofu.